Evaluation of topical antioxidants and packaging materials to decrease the incidence of bone discoloration in pork retail cuts - C R Raines; Michael E Dikeman (Kansas Agricultural Experiment Station Research Reports, 2004)
Color characteristics were evaluated on 48 pork backbones. After 6 d postmortem, six 1- inch-thick sections of lumbar vertebrae were cut from each backbone. Lumbar vertebrae were treated with different concentrations of ascorbic acid, with combination treatments of ascorbic acid and natural antioxidants, or left untreated. Bones were packaged in one of three systems: high-oxygen modifiedatmosphere packaging (MAP), ultra-lowoxygen MAP, or polyvinyl chloride (PVC) overwrap trays. Bones were visually evaluated by a trained panel on d 0, 1, 2, 3, 4, 5, and 8. Lightness (L*) was also measured on d 0, 2, and 8 of display. After 8 d of display, antioxidant- treated bones packaged in highoxygen MAP were more desirable than those in PVC overwrap trays. Bones packaged in ultra-low-oxygen MAP became less desirable over 8 d of display. Solutions of 1.875% and 2.50% ascorbic acid yielded the most desirable color after 8 d for bones in high-oxygen MAP and in PVC overwrap trays. Bones treated with 1.875% or 2.50% ascorbic acid tended to have lighter color (higher L*) on d 8 for high-oxygen MAP and PVC overwrap trays, whereas an overall difference was not observed for lightness for bones packaged in ultra-low-oxygen MAP.; Swine Day, 2004, Kansas State University, Manhattan, KS, 2004
Keywords: Swine day; 2004; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 940; Kansas Agricultural Experiment Station contribution; no. 05-113-S; Bone color; Modified atmosphere packaging; Antioxidant; Pigs; Swine